Writing Recount Text: A Case Study of Grammatical Errors of ELT Classroom at 10th Grade Students - Misa, Mikhael (Budapest International Research and Critics University, 2022)
This study was conducted to examine the types of grammatical errors and to determine the challenges associated with grammatical errors in recount texts written by students. This study employed a descriptive quantitative method. The researcher sent the text to students in grade 10th as part of the data collection process. The text must be produced using the Orientation, Events, and Reorientation of the pattern common in recount texts. The students have 60 minutes to write a text recounting an exceptional life occurrence. There should be at least three paragraphs in the text (Orientation, Events, Re-orientation). The researcher then calculated the writing errors the students had produced using a straightforward statistical calculation. The findings of this study demonstrate that students made errors in some areas when writing recount texts, including errors in Punctuation and Spelling, with the highest errors by 20 (100%) students, the second errors in Tense by 17 (85%) students, the third errors in Sentence Pattern by 15 (75%) students, the fourth is errors in Preposition by 11 (55%) students and the last errors in Pronoun with only 4 (20%) student. Moreover, the students got a score of 183 (45.75%). It indicated that the student's level of mastery could be poor. Furthermore, it recommended that the students should learn more about English grammar and that the teacher should improve their teaching and learning techniques to reduce the students’ Errors.